Rancang Bangun Pendeteksi Kebakaran dan Pemadam Api Otomatis Dua Zona Berbasis Arduino - Apri Mardoni; Sari Novalianda; Yoga Tri Nugraha; Arif Milando Setiawan (Jurnal Rekayasa Lampung, 2026)
Fires are disaster that often in Indonesia, mainly caused by electrical short circuit, gas leaks, and other factors due to the increased use of electronic devices. This study recommends a fire detection system based on Arduino Uno that uses two flame sensors to detect fire intensity in two different zones. The goal of this research is to design and test a fire detection system that is responsive and can provide notifications and early warnings, as well as automatically respons by activating a buzzer for alerts and a solenoid valve and water pump for extinguishing. The research stages include selecting sensors, analyzing system requirements, verifying the program, building the system, and testing at various distances from the fire source. The research show that the system can respond quickly to fires because it can automatically extinguish flames in zones where fire is detected. Testing the flame sensors at various distances confirmed the system’s success in detecting fire from 0 cm to 100 cm. Integration with a LCD I2C 20 x 4 enhances the system’s ability to monitor events in real time and take appropriete action. In conclusion, the design and build of Arduino Uno based automatic fire detection and extinguishing system can be highlighted as an effective solutions for handling fire hazards. This design has great potential for early fire detection.